Anatolian Languages as the Main Substrate of the Ukrainian Language - Viktor Lakyziuk (Українознавство, 2020)
Until now, the Ukrainian linguistics has claimed that the main substrate for the Ukrainian language is North Iranian / Scythian. This dominant opinion was based on the well-known hypothesis of the Soviet school philologists and, in particular, of the Ossetian linguist Vaso Abaiti (better known as Vasyl Abaev (Abayev)) about the Iranian origin of the Scythian language. The scholar insisted that the Ossetian language descended from the hypothetical Scythian-Sarmatian one, and tried to explain the names of the largest waterways not only of the Black Sea region but also of the entire Ukraine and Eastern Europe using only Iranian-Ossetian words. The author of the article has prepared a number of materials to refute this false claim of modern researchers. In this respect, undoubtedly helpful is a unique artifact, a prehistoric inscription discovered ten years ago in the basement of a temple in the regional center, Zhytomyr. It turned out that the modern Ukrainian vocabulary contains a large number of words whose meanings and sounds are almost identical to the Anatolian glosses – Phrygian, Lydian, Thracian, Lycian A and Lycian B (Milyan), Carian, as well as the preceding languages – Hattic/Hattian and Luwian/Luvian. As evidenced by the lexical material of the Phrygian-Ukrainian dictionary, prepared by the author of the article, most of such related words (full cognates) are observed in these two languages – Phrygian and Ukrainian. Thus, another false linguistic statement is refuted which most closely relates Ancient Greek to Phrygian. It was made by linguists relying on forty Greek words that sound similar to Phrygian. The proposed study provides striking discoveries: more than a half of the Old Phrygian words known today have entered the vocabulary of the Ukrainian language. Why has it been concealed before? It turns out that the researchers have so far compared Phrygian only with Greek, Armenian, Old Macedonian, Albanian; however, for some reason, no one dared call it the closest relative of the Ukrainian language. This might have been prevented by the fact that, by Herodotus’ definition, Phrygian was considered “the most ancient language of the world”.